Fighting for Honor : The History of African Martial Arts in the Atlantic World - Desch-Obi, M. Thomas J. (Book collections on Project MUSE., 2021)
The presence of African influence and tradition in the Americas has long been recognized in art, music, language, agriculture, and religion. T. J. Desch Obi explores another cultural continuity that is as old as eighteenth-century slave settlements in South America and as contemporary as hip hop culture. In this thorough survey of African martial arts techniques, Obi maps the translation of numerous physical combat techniques across three continents and several centuries to illustrate how these practices evolved over time and are still recognizable in American culture today. Some of these art traditions were part of African military training while others were for self-defense and spiritual discipline. Grounded in historical and cultural anthropological methodologies, Obi's investigation traces the influence of well-delineated African traditions on long-observed but misunderstood African and African American cultural activities in North America, Brazil, and the Caribbean. He links the Brazilian martial art capoeira to reports of slave activities recorded in colonial and antebellum North America. Likewise Obi connects images of the kalenda stick-fighting techniques to the Haitian revolution. Throughout the study Obi examines the ties between physical mastery of these arts and changing perceptions of honor. Including forty-two illustrations, this rich history of the arrival and dissemination of African martial arts in the Atlantic world offers a new vantage for furthering our understanding of the powerful influence of enslaved populations on our collective social history.